Fabrication techniques and morphological analysis of perovskite absorber layer for high-efficiency perovskite solar cell: A review - Jamal M.S.; Bashar M.S.; Hasan A.K.M.; Almutairi Z.A.; Alharbi H.F.; Alharthi N.H.; Karim M.R.; Misran H.; Amin N.; Sopian K.B.; Akhtaruzzaman M. (Elsevier Ltd, 2023)
Convergence of numerical methods; Conversion efficiency; Crystallization; Energy harvesting; Fabrication; Lead compounds; Morphology; Perovskite; Photons; Solar cells; Solar energy; Stability; Anti-solvents; High power conversion; Morphological analysis; Morphological properties; Photon-to-current conversion efficiency; Power conversion efficiencies; Structure and morphology; Technological challenges; Perovskite solar cells